Book Review: A Guide in Conducting Basic Research - Bahtiar Bahtiar; David Ackah; Pius Weraman (Aloha International Journal of Health Advancement (AIJHA), 2025)
Beginner researchers and health students need guidebooks to be able to carry out basic research well, so basic research guidebooks are very important. This study aims to review a basic research guidebook. The review is carried out using a systematic method including a summary of the book, advantages, disadvantages and suggestions for improvement. The results of the review show that in general this guidebook is good, but there are still shortcomings in terms of structure, information and lack of examples. It is concluded that this book is very important and needs to be updated immediately to eliminate existing deficiencies. Keywords: basic research; guide book; beginner researcher; health student